Sharing the Eucharist? Critical Comments from a Canonical Perspective on the Statement "Together at the Lord’s Table" (2019) of the Ecumenical Study Group of Protestant and Catholic Theologians - Dvořáček, Jiří 1973- (2022)
The following article analyses the statement of the Ecumenical Study Group of Protestant and Catholic Theologians entitled "Together at the Lord’s Table" (2019) from the perspective of canon law of the Latin Church. First, it briefly presents the content of the statement, then it summarises the opinion of the Congregation for the Doctrine of the Faith. The article shows that the alternate participation in the Protestant and Catholic service of celebrating the Lord’s Supper / Eucharist by virtue of baptism alone is problematic from the perspective of Catholic canon law. Canon law builds on Catholic ecclesiology and sacramentology, based on the connection between baptism and the Church as well as the Church, the ministerial priesthood, and the celebration of the Eucharist. The article, then, shows the instruments of canon law for the protection of the Catholic faith regarding the apostolic succession as the only valid condition for presiding over the Eucharistic community and the Eucharist as the substantial presence of Christ. In the final chapter, the implications of participation in ecumenical worship for the Catholic faithful will be summarised. The participation of Protestants in Catholic worship, as proposed by the Statement, is not explicitly regulated by canon law. The CIC, in Canon 844 § 4, lays down only the conditions under which Protestants may licitly receive selected sacraments (the Eucharist, the anointing of the sick and the sacrament of penance), while for a valid reception of the Eucharist their baptism alone enables them.
Keywords: "Together at the Lord’s Table"; Canon Law; Ecumenism; Intercommunion; norms on reserved crimes